Analisis Indeks Kepuasaan Masyarakat Pada Layanan Kepengurusan Surat Keterangan Tanda Lapor Kehilangan (SKTLK) di Polsek Jambangan - Kusuma Dewi, Novian; Noviyanti (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
The problems that exist in the service of managing the Certificate of Loss Report (SKTLK), Polsek Jambangan has not implemented the IKM, lack of human resources which results in less than optimal service, lack of publication related to information about the service of managing the Certificate of Loss Report (SKTLK) and lack of infrastructure. Therefore, the purpose of this study is to describe and analyze the results of the Community Satisfaction Index (SMI) on the service of managing the Certificate of Loss Report (SKTLK) at the Jambangan Police. This research uses a quantitative approach with a survey method. In this study to measure public satisfaction with the services provided by Jambangan Police is to use the Community Satisfaction Index in accordance with the Regulation of the Minister of Administrative Reform of Bureaucratic Reform (Permenpan RB) Number 14 of 2017 concerning Guidelines for Preparing Community Satisfaction Surveys for Public Service Delivery Units. The sampling technique used Accidental Sampling with a population of 250 people and a sample size of 71 people using data collection techniques in the form of questionnaires. The results showed that the Community Satisfaction Index at Jambangan Police fell into the "GOOD" category with an interval value of 81.57. Suggestions given to Jambangan Police in improving elements that have not fully run smoothly.